Comparison of Brain Targeted Teaching Model V/S Students’ Content Schemata with Online Instruction in Reading to Students Different Motivation Level - Rukminingsih Rukminingsih; Januarius Mujiyanto; Joko Nurkamto; Rudi Hartono (Universitas Negeri Semarang, 2021)
The purpose of this research is to study the effects of brain targeted teaching (BTT) model v/s activating students’ content schemata v/s in online to teach reading comprehension to students with different motivation level in one of private college in Indonesia. The participants of this research were students who were taking Critical Reading class. Class A was as the experiment class 1 and class B was as experiment class two. Every class consisted of 30 students (15 high and 15 low motivation level). This study was experimental research design by using 2 x2 factorial designs. The data collection was done by give questionnaire reading motivation level and reading comprehension test. The data was analyzed by ANOVA. The study revealed results that the BTT model and activating student content schemata were effective to teach reading comprehension to high and low students’ motivation level. BTT model gave better effect than activating students’ content schemata with high and low motivation level. The last there was an interaction between teaching techniques, students’ critical reading achievement and motivation level. In conclusion, both BTT model and activating students’ content schemata were effective applied in teaching reading achievement to students with high and low motivation level.